Durability of S-RBD IgG Antibody Levels after Sinovac Vaccination in Healthcare Workers - Nugraha, Jusak; Permatasari, Cynthia Ayu; Fitriah, Munawaroh (Folia Medica Indonesiana, 2022)
Highlights: • The effectiveness of vaccination through the kinetics of the antibody response to the SARS-COV-2 vaccine administration by examining IgG S-RBD levels was aimed. • Two doses of the Sinovac vaccine formed antibodies in healthy individuals in the first 3rd month after vaccination. • An S-RBD IgG antibody in the 6th-month post-vaccination was significantly different between groups without a history and groups with a history of infection with COVID-19. Abstract: Since it was declared a pandemic in early 2020, Coronavirus Disease 2019 (Covid-19) has caused high morbidity and mortality in the world. In view of the urgency of the situation, vaccination efforts are needed to break the chain of disease transmission. Various types of vaccines have been successfully developed and obtained approval for emergency use. However, the effectiveness of these vaccines, both in the short and long term, has not been fully known. This study aimed to examine the effectiveness of vaccination through the kinetics of the antibody response to the administration of the SARS-COV-2 vaccine by examining IgG S-RBD levels. This study was an observational analytic study with a prospective cohort approach carried out between January and November 2021 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Fifty health workers who received Sinovac vaccination in as many as 2 doses underwent venous blood taking and measurement of quantitative S-RBD antibody level. Then, quantitative S-RBD IgG antibody levels were measured and recorded in each subject. The mean S-RBD IgG antibody was found to have fluctuation. The titer was found to significantly increase on day 14 and dropped significantly in month 3 (p <0.001). There was a significant difference in S-RBD IgG levels 6 months after vaccination between Covid-19 uninfected groups and Covid-19 infected groups (p <0.001). In a conclusion, two doses of the Sinovac vaccine formed antibodies, although humoral immunity obtained tended to decrease in 3rd month after vaccination to healthy individuals. The average level of S-RBD IgG antibody in the sixth month post-vaccination was found to be significantly different between groups without history and groups with a history of with infection COVID-19.